2018
DOI: 10.1007/s40620-018-0530-2
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB activation contributes to parathyroid cell proliferation in chronic kidney disease

Abstract: NF-κB plays an important role in PG hyperplasia progression. VDR deficiency may be involved in the parathyroid gland hyperplasia through the activation of NF-κB pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…NF-κB contributes to the pathogenesis of primary parathyroid hyperplasia [ 99 ]. In CKD-induced SHP, parathyroid glands from patients on dialysis showed activation of the NF-κB pathway in the nodular hyperplastic glands, with a significantly higher increase in diffuse hyperplastic glands [ 100 ]. In 5/6 nephrectomized rats fed a high-phosphorus diet, Proliferating cell nuclear antigen (PCNA) levels and activation of the NF-κB pathway were higher compared with the sham group, and VDR levels were decreased as expected.…”
Section: Post-receptor Mechanisms Of Parathyroid Cell Proliferatiomentioning
confidence: 99%
See 1 more Smart Citation
“…NF-κB contributes to the pathogenesis of primary parathyroid hyperplasia [ 99 ]. In CKD-induced SHP, parathyroid glands from patients on dialysis showed activation of the NF-κB pathway in the nodular hyperplastic glands, with a significantly higher increase in diffuse hyperplastic glands [ 100 ]. In 5/6 nephrectomized rats fed a high-phosphorus diet, Proliferating cell nuclear antigen (PCNA) levels and activation of the NF-κB pathway were higher compared with the sham group, and VDR levels were decreased as expected.…”
Section: Post-receptor Mechanisms Of Parathyroid Cell Proliferatiomentioning
confidence: 99%
“…1,25D decreased serum PTH and parathyroid cell proliferation together with reduced activation of the NF-κB pathway. A selective NF-κB inhibitor PDTC (ammonium pyrrolidinedithiocarbamate) decreased parathyroid NF-κB pathway activation, serum PTH, parathyroid cell proliferation, and the enlargement of the parathyroid glands in 5/6 nephrectomized rats [ 100 ]. These findings suggest that NF-κB contributes to parathyroid cell proliferation.…”
Section: Post-receptor Mechanisms Of Parathyroid Cell Proliferatiomentioning
confidence: 99%
“…NF-κB contributes to the pathogenesis of primary parathyroid hyperplasia [140]. In CKD-induced SHP, there was activation of the NF-κB pathway in the nodular hyperplastic parathyroid glands from patients on dialysis, with a significant increase in diffuse hyperplasia glands [141]. The reduction in VDR could lead to activation of the NF-κB pathway.…”
Section: Nuclear Factor-kappa Bmentioning
confidence: 99%
“…In regard to the signaling mechanisms involved in the development of parathyroid hyperplasia, a recent study by Kan et al . reported that vitamin D deficiency promotes activation of nuclear factor kappa B (NFκB) both in parathyroid glands from patients on hemodialysis and in experimental models of uremia 23 . Given that vitamin D also inhibits NFκB in other tissues 24 , this might represent an additional benefit of vitamin D supplementation in the management of SHPT.…”
Section: Novel Insights Into the Pathogenesis Of Secondary Hyperparatmentioning
confidence: 99%